Disseminating and Using Student Assessment Information in The Gambia - Senghor, Ousmane (World Bank, Washington, DC, 2014)
The Gambia has shifted the focus of its education reforms from school attendance to student learning. This shift came with a stronger assessment system to measure learning. This paper highlights how assessment data are being used in The Gambia to contribute to education quality and learning. While assessment data were used mainly for selection purposes in the past, the emphasis now is on monitoring and supporting learning. Greater data availability has allowed for greater school accountability as well as for more systematic feedback on the curriculum and teacher training. Several factors converged to allow for more effective use of assessment data, including a favorable political environment, the development of strategic partnerships, and the building of local assessment capacity.